中小學教師專業學習社群運作與成效之研究： 社群召集人觀點 Effectiveness of Teachers' Professional Learning Communities on Primary and Secondary School Performance from the Perspective of Professional Learning Community Leaders - 江姮姬 Heng-Chi Chiang (National Changhua University of Education, 2024)
本研究係探究109學年度中小學教師專業學習社群之運作成效，以問卷調查社群召集人，採Stufflebeam CIPP評鑑模式設計問卷，抽樣調查3,589位，以描述性統計、卡方檢定、逐步多元迴歸分析進行分析。本研究問題為：一、召集人培訓、運作內容、運作型式與運作成效四個變項之成效為何？二、召集人培訓與運作因素是否具顯著相關？三、運作因素對教與學助益、成員持續參與的預測力？根據分析結果，本研究結論為：一、召集人培訓、運作內容、運作型式與運作成效四個變項成效顯著。二、召集人培訓結果與運作因素具顯著相關。三、運作因素對教與學助益、成員持續參與具顯著影響力。 This study investigates the effectiveness of teachers' professional learning communities（PLCs）from the perspective of primary and secondary school PLC leaders. This study's research design employs the context, input, process, and product（CIPP）program evaluation model to answer three research questions: 1. What are the effects of the four variables of PLC leader, PLC operation content, PLC operation type, and PLC operation effectiveness-on school PLC performance? 2. Is there a significant correlation between PLC leader training and PLC operation factors? 3. What is the predictive power of PLC operation factors on teaching and learning benefits and on members' continuous participation? The research findings show that 1. the training of PLC leaders, the operation content, the operation type, and the operation effect of PLC are all important effect on school PLCs. 2. The training results of PLC leaders are significantly correlated with factors of PLC operation. 3. The factors of PLC operation have a fundamental impact on both teaching and learning benefits as well as sustained participation of PLC members.